Factors Affecting Employment Waiting Period for the Graduates of DIII Accounting of State Polytechnic of Lampung - Rusmianto Rusmianto; Damayanti Damayanti; Irawan Irawan (Politeknik Negeri Lampung, 2015)
This study is to empirically test the effect of cumulative GPA, English language skills, and gender toward the employment waiting period of the graduates of DIII Accounting of State polytechnic of Lampung. This research was conducted on the batches III to V of graduates of Diploma in Accounting of State Polytechnic of Lampung. A multiple regression model was used to test the hypothesis proposed. The results indicate that Academic ability (GPA ) and English language proficiency give a negative effect on employment waiting period of the graduates, while gender did not affect differently.Keywords : employment waiting period, GPA , English language proficiency : gender